Flow cytometric evaluation of Calotropis gigantea for determining its antimicrobial activities in infected human whole blood samples - Amit Gupta; Sushama R Chaphalkar (Shahrekord University of Medical Sciences, 2017)
Introduction: Medicinal plants are considered to be safer, non-toxic and less harmful as compared to synthetic based drugs that are available. In this study, we focused on aqueous leaves extract of Calotropis gigantea for determining its antimicrobial activity in infected (dengue) human whole blood samples using flow cytometry. Methods: Infected dengue human blood samples (n = 5; confirmed on the basis of NS1 antigen to dengue virus;) were collected from pathology lab and evaluated its blood counts (lymphocytes, monocytes and granulocytes count); forward scatter (FSC) and side scatter (SSC) including CD14 monocyte surface marker following the use of variable doses of aqueous leaves extract of C. gigantea. Results: In this study, the results showed that aqueous leaves extract of C. gigantea caused enhancement in case of granulocytes FSC (shape and size) and SSC (granularity) counts but this aqueous extract inhibited CD14 monocyte surface marker population at higher doses. In contrast, dengue infected human blood samples used as control showed sudden decline in granulocytes count but there was enhancement in CD14 monocyte surface marker as compared to control group. Conclusion: Overall, C. gigantea in the form of aqueous leaves extract showed anti-dengue activity in infected human whole blood samples.